Genomic insights into an endophytic Streptomyces sp. VITGV156 for antimicrobial compounds - Veilumuthu, Pattapulavar; Nagarajan, T.; Magar, Sharayu; Sundaresan, Sasikumar; Moses, Lenus Joy; Theodore, Thomas; Christopher, John Godwin (Frontiers in Microbiology, 2024)
Endophytic Streptomyces spsspp. are recognized as a potential resource of valuable natural products, yetbut are less explored. This study focusesfocused on exploring endophytic Streptomyces species residing within tomato plants (Solanum lycopersicum) havingharboring genes for the production of a novel class of antibiotics. Our research work resulted ininvolved the isolation and characterization of Streptomyces sps VITGV156, a newly identified endophytic Streptomyces species, producing that produces antimicrobial products. VITGV156 harbors a genome of 8.18 mb and codes forencodes 6512 proteins, of which 4993 proteins of known function (76.67%), and 1519 proteins (23.32%) of unknown function. By employing genomic analysis, we elucidate the genome landscape of this microbial strain, and shed light on various BGCs responsible for producing polyketide antimicrobial compounds, with particular emphasis on the antibiotic kendomycin. We extended our study onby evaluating the antibacterial properties of kendomycin. Overall, this study provides valuable insights into the genome of endophytic Streptomyces species, particularly Streptomyces sps VITGV156, aswhich are prolific producers of antimicrobial agents. These findings hold promise for further research and exploitation in pharmaceutical compounds, offering opportunities for the development of novel antimicrobial drugs.